The Effectiveness of FluentU Application on Students’ Vocabulary Mastery for Ninth Grade Students at SMPN 9 Bekasi - Ferawaty Puspitorini; Hermariyanti Kusumadewi; Nurhayati (Candradimuka: Journal of Education, 2026)
This research focuses on evaluating the role of the FluentU application in the improvement in improving vocabulary mastery among ninth-grade students at SMPN 9 Bekasi. Mastery of vocabulary is central to learning English, as it supports students’ ability to understand, communicate, and the four core language skills: reading, writing, listening, and speaking. However, many students still encounter difficulties in mastering sufficient vocabulary, which limits their overall English proficiency. To address this issue, technology-based media such as FluentU can provide an innovative learning approach. This study employed a quasi- experimental methodology with two groups: an experimental group that was learned through  FluentU and a control group that was taught using conventional methods. The instruments used in data collection were pre-tests and post-tests, which measured students’ vocabulary mastery before and after the treatment. The findings revealed that students results indicated that the experimental group outperformed the control group with a statistically significant difference. The interactive features of FluentU, such as authentic videos, captions, and quizzes, helped students to learn vocabulary in meaningful contexts, thus enhancing both retention and understanding. Moreover, students demonstrated greater motivation and engagement exhibited by students during instructional activities when using the application. These results suggest that the FluentU application is an effective tool for supporting vocabulary learning among junior high school students. Therefore, it is recommended that English teachers integrate digital learning platforms like FluentU into classroom activities to enrich vocabulary instruction and encourage independent learning.